Discarding images: reflections on music & culture in medieval France - Page, Christopher 1952- (Oxford Clarendon Press, 1993)
For many centuries, the Western imagination has pictured the medieval period as a kind of odyssey: a journey that took humankind to a strange country and ended in the Renaissance with its homecoming and the restoration of its inheritance. In this stimulating and provocative book, Christopher Page, Director of the acclaimed early music vocal group Gothic Voices, explores the kinds of generalizations that we habitually make about "the Middle Ages" and which, whether we know it or not, sustain the false image of a medieval odyssey. In chapters that proceed chronologically from the thirteenth to the fifteenth century, he examines what we suppose to be the serenity of medieval reflection on such matters as the "numerical" explanation of musical beauty, and he questions the modern tendency to regard Ars antiqua motets as music for "an intellectual elite." Turning to the Ars Nova and beyond, he discusses the relation between fourteenth century innovations and contemporary science. A final chapter explores the powerful influence of Johan Huizinga's classic The Waning of the Middle Ages upon musicology. Page's lively prose is full of provocative ideas, and is enriched by an uncommonly deep experience of medieval music.
Keywords: Grocheo, Johannes de; Middle Ages (500-1400); 15th Century (1401-1500); Music history; Motet; Ars nova; Ars Antiqua; Song; France